2014
DOI: 10.1186/1880-5981-66-15
|View full text |Cite
|
Sign up to set email alerts
|

Polybaric crystallization differentiation of H2O-saturated island arc low-K tholeiite magmas: a case study of the Izu-Oshima volcano in the Izu arc

Abstract: Island arc low-K tholeiites are basaltic magmas erupting from frontal arc volcanoes of juvenile arcs associated with the subduction of old and cold plates. We investigated the origins of geochemical variation in volcanic rocks having multiple phase saturated liquid compositions from the Izu-Oshima volcano in the northern Izu arc. The geochemical variations in the liquids fall between two endmember trends, namely higher-and lower-Al/Si trends. Polybaric differentiation of H 2 O-saturated melts between a 4-km-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…We propose a new model for the SHV system with an emphasis on the role of deeply generated volatiles, the idea of a mature magma system with magma and magmatic fluid accumulation and generation at multiple levels, and destabilization of the system leading eventually to a major eruption. Our model builds on: models of multiple magma chambers and igneous mush systems [Hildreth, 2004;Marsh, 2004;van der Zwan et al, 2013;Walker et al, 2013;Jaxybulatov et al, 2014;Cashman and Giordano, 2014]; concepts of polybaric differentiation [Pichavant et al, 2002;Grove et al, 2005;Ulmer, 2007;Gertisser et al, 2012;Almeev et al, 2013;Hamada et al, 2014;Melekhova et al, 2015]; separation of melts and fluids from low porosity source regions into inherently unstable melt-rich layers or lenses [Solano et al, 2012;Connolly and Podladchikov, 2013]; and segregation of magmatic fluids from underplated magmas including basalt and andesite derived by fractionation of basalt [Bachmann and Bergantz, 2006]. Figure 6 shows a schematic depiction of the envisaged trans-crustal magmatic mush system.…”
Section: Magmatic System Modelmentioning
confidence: 99%
“…We propose a new model for the SHV system with an emphasis on the role of deeply generated volatiles, the idea of a mature magma system with magma and magmatic fluid accumulation and generation at multiple levels, and destabilization of the system leading eventually to a major eruption. Our model builds on: models of multiple magma chambers and igneous mush systems [Hildreth, 2004;Marsh, 2004;van der Zwan et al, 2013;Walker et al, 2013;Jaxybulatov et al, 2014;Cashman and Giordano, 2014]; concepts of polybaric differentiation [Pichavant et al, 2002;Grove et al, 2005;Ulmer, 2007;Gertisser et al, 2012;Almeev et al, 2013;Hamada et al, 2014;Melekhova et al, 2015]; separation of melts and fluids from low porosity source regions into inherently unstable melt-rich layers or lenses [Solano et al, 2012;Connolly and Podladchikov, 2013]; and segregation of magmatic fluids from underplated magmas including basalt and andesite derived by fractionation of basalt [Bachmann and Bergantz, 2006]. Figure 6 shows a schematic depiction of the envisaged trans-crustal magmatic mush system.…”
Section: Magmatic System Modelmentioning
confidence: 99%
“…The origin of anorthite in MORB, near-ridge seamounts, calc-alkaline and tholeiitic arc volcanoes, and even boninites has been debated over the last decades [e.g., Allan et al, 1989;Danyushevsky et al, 1997;Donaldson and Brown, 1977;Hamada and Fujii, 2007;Nielsen et al, 1995;Ushioda et al, 2014]. Several parameters can influence the An content in plagioclase, i.e., the Ca/Na and Al/Si ratios in the coexisting melt, crystallization temperatures, pressures, and H 2 O contents of the melt [e.g., Danyushevsky Hamada and Fujii, 2007;Hamada et al, 2014;Marsh et al, 1990;Panjasawatwong et al, 1995;Sisson and Grove, 1993]. Higher temperatures and higher H 2 O contents generally lead to higher An contents, whereas increasing pressures lead to decreasing An content [e.g., Panjasawatwong et al, 1995;Sisson and Grove, 1993].…”
Section: The Origin Of Anorthitementioning
confidence: 99%
“…since the caldera formation. Hamada et al (2014) examined the compositional variations of melt for all volcanic activity at Izu-Oshima, and found that the melt compositions fall within the area comprised between higher-and lower-Al/Si trends in compositional variation diagrams. Hamada (2016) attributed the higher-and lower-Al/Si trends to crystallization differentiation of magmas at the 8-10 km depth and ∼4 km depth magma chambers, respectively, which was controlled by the stability of plagioclase relative to mafic minerals.…”
Section: Previous Studymentioning
confidence: 99%
“…The Izu-Oshima volcano, located on the volcanic front of the Izu arc (Figure 1), is one of the most active volcanoes in Japan, and younger volcanism (<∼1.5 ka) has produced mainly basaltic magmas with minor basaltic andesitic magmas. Relatively largescale eruptions, in the order of 10 5 -10 6 m 3 of eruption volume, have occurred every 30-40 years for the past 200 years (1876-77, 1912-14, 1950-51, and 1986-87), and eruptions are expected to occur in the near future; therefore, many petrological and geochemical studies have been conducted to understand the magma plumbing system beneath the volcano (e.g., Fujii et al, 1988;Kawanabe, 1991;Nakano and Yamamoto, 1991;Hamada et al, 2011Hamada et al, , 2014Ishizuka et al, 2015). Our knowledge of magmatic processes has greatly advanced as a result of these studies, and there is now a consensus that basaltic magmas and basaltic andesitic magmas are stored in a main magma chamber located at 8-10 km depth and small magma bodies located at 4-5 km depth, respectively, and new magmas have been intermittently supplied to the main 8-10 km-deep magma chamber from a deeper magma chamber (Meteorological Agency, 2008;Hamada, 2016).…”
Section: Introductionmentioning
confidence: 99%